PENGARUH PENERAPAN MODEL DISCOVERY LEARNING MENGGUNAKAN TRUE OR FALSE STATEMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TANJUNG BALIT KABUPATEN SOLOK TAHUN PELAJARAN 2014/2015 - ASNITA, YULIA - (Pendidikan Matematika, 2014)
This research was motivated by the students understanding of mathematicalconcepts are still low. The purpose of the research to know is it have influence themathematical concept understanding by doing discovery learning model, be usingtrue or false statement to class VIII Islamic junior higt school Tanjung BalitKabupaten Solok. The kind this research is eksperiment research with preeksperimentdesigh method : pre-test and pos-test. Population in this research isthe student class VIII Islamic junior high school 2014/2015. To select the samplesthis research uses random sampling, the choose is class VIII.1. Researchinstrument be using test it is essay with competence indicator of conceptunderstanding. The data process to analisys with t-test. Based on productresearch to get data analisys to know so test hipotesis = 0,05, it get value thitung= 3,77 so not deal H0 and deal H1. So that in condution the influence conceptunderstanding studentâs mathematical be model discovery learning technique beusing true or false statement for concept understanding class VIII Islamic juniorhigh school Tanjung Balit.